Anesthetic Management for Thoracotomy in A Geriatric Patient with Bronchiectasis who Underwent Lobectomy Complicated by Severe Aortic Stenosis: A Case Report - Joseph Rusli; Angela Mulyana Sugiaman; Arfian Pascalis Kurniawan; Indra Hapdijaya; Julia Windi Gunadi (Sound of Health Journal, 2025)
Bronchiectasis, characterized by the abnormal and permanent dilation of the bronchi and the destruction of the elastic and muscular layers of the bronchial wall, often arises from infections such as tuberculosis and pneumonia. This condition can lead to significant morbidity and potential mortality due to loss of lung function. Surgical intervention could be considered in cases of failed medical therapy or persistent symptoms. Anesthetic management for thoracotomy and lung resection in these patients is crucial, particularly when complicated by severe aortic stenosis (SAS), which poses additional risks for perioperative complications. This condition requires careful anesthetic strategies to optimize outcomes. In this case report, a 77-year-old male with chronic bronchiectasis and severe aortic stenosis was scheduled for elective thoracotomy lobectomy. The patient experienced persistent cough and dyspnea, with preoperative spirometry indicating moderate restriction. Echocardiography revealed critical aortic stenosis and low ejection fraction, indicating high surgical risk. Anesthesia induction involved fentanyl, midazolam, and atracurium, followed by intubation with a left-sided double-lumen tube for one-lung ventilation. Intraoperatively, hemodynamic stability was maintained with dobutamine and nitroglycerin. The patient successfully underwent a thoracotomy lobectomy lasting approximately 4.5 hours with manageable blood loss. He was transferred to the ICU for postoperative care and was extubated on the second postoperative day. He was discharged on the tenth postoperative day without complications. This case highlights the importance of hemodynamic stability in patients with bronchiectasis and severe aortic stenosis undergoing thoracotomy lobectomy. Careful anesthetic management and monitoring are crucial to prevent complications, and dobutamine and nitroglycerin effectively maintain stability during surgery for better outcomes.